2014
DOI: 10.5194/se-5-873-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of magma activation beneath the Harrat Lunayyir basaltic field (Saudi Arabia) from attenuation tomography

Abstract: Abstract. We present a seismic attenuation model for the crust beneath the Cenozoic basaltic field of Harrat Lunayyir (western Saudi Arabia), where a strong seismic swarm occurred in 2009. The tomography inversion uses the envelope shape of the S wave seismograms from over 300 strong events (M < 3.5). The resulting attenuation structures appear to be consistent with the distribution of seismic velocities. The obtained 3-D attenuation model distinguishes the low-attenuation zones down to 5 km depth correspondin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Lateral migration of magma before or during the eruptions is documented in a series of papers (Ishizuka et al, 2008;Grandin et al, 2011, González et al, 2013, Caudron et al, 2015, McGee et al, 2015. Most well-known examples of such migration are recorded for Iceland volcanoes (Einarsson and Brandsdottir, 1980;Sigmarsson et al, 2000;Sigmundsson et al, 2015), during volcanic unrest stage before submarine eruption near El Hierro island (Martí et al, 2013;González et al, 2013;García-Yeguas et al, 2014;Ibanez et al, 2012), during Manda-Hararo-Dabbahu rift activity in Ethiopia in 2005-2011 (Grandin et al, 2011;Passarelli et al, 2014) and in Lunayyir MVF in 2009 in Saudi Arabia (Pallister et al, 2010;Zobin et al, 2013;Koulakov et al, 2014Koulakov et al, , 2015. Another, fundamental, difference between MVF and polygenetic type of activity is the absence of the focused central feeding vent.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral migration of magma before or during the eruptions is documented in a series of papers (Ishizuka et al, 2008;Grandin et al, 2011, González et al, 2013, Caudron et al, 2015, McGee et al, 2015. Most well-known examples of such migration are recorded for Iceland volcanoes (Einarsson and Brandsdottir, 1980;Sigmarsson et al, 2000;Sigmundsson et al, 2015), during volcanic unrest stage before submarine eruption near El Hierro island (Martí et al, 2013;González et al, 2013;García-Yeguas et al, 2014;Ibanez et al, 2012), during Manda-Hararo-Dabbahu rift activity in Ethiopia in 2005-2011 (Grandin et al, 2011;Passarelli et al, 2014) and in Lunayyir MVF in 2009 in Saudi Arabia (Pallister et al, 2010;Zobin et al, 2013;Koulakov et al, 2014Koulakov et al, , 2015. Another, fundamental, difference between MVF and polygenetic type of activity is the absence of the focused central feeding vent.…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation structure beneath Sierra Negra is imaged with the spectral decay method. Despite difficulties in modeling and high scatter, this method has successfully imaged attenuation structures in various volcanic media [e.g., De Siena et al , , ; Koulakov et al , ; Ohlendorf et al , , Lin et al , ]. We interpret our Qp1 model in context of current V p [ Tepp et al , ] and models of surface deformation [ Amelung et al , ; Yun et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…These fields are predominantly composed of alkali olivine basalt (Koulakov et al 2014) and tholeiitic basalt (Al-Amri and Fnais 2009) lava flows. Harrat Lunayyir is located in the western region of the Arabian Plate and is composed of Neogene and Quaternary basaltic lava flows that cover the Neoproterozoic basement (Koulakov et al 2014). Lunayyir is one of the youngest Harrats in the region, exhibiting a more diverse composition.…”
Section: Geological Setting Of Harrat Lunayyirmentioning
confidence: 99%
“…Previous models (Baer and Hamiel 2010;Pallister et al 2010) have inferred that dyke intrusion is based on the fact that seismic events in the area tended to form a linear structure oriented toward the southern part of the harrat. In light of this, Koulakov et al (2014) modelled the distributions of P-wave to S-wave velocities in the area and concluded that it is not possible to directly confirm whether the dyke intrusion took place in 2009. Based on their research and Fig.…”
Section: Dyke Intrusion and Other Hypothesesmentioning
confidence: 99%